OF ESSENTIAL OILS FROM PLANTS AND THEIR CHANGE WITH VEGETATIVE PHASES AS AN EXAMPLE OF ASIAN MINT (MENTHA ASIATICA BORISS) - H.K. Dzhumaev, G.E. Umirzakova (Journals Park Publishing, 2022)
Mentha asiatica Boriss. in two phases received essential oils: in the phase of vegetation and flowering. The aboveground part in the phase of the growing season contains 0.10%, in the leaves - 0.13%; the phase in the aboveground part flowering contains 0.14%, in the leaves - 0.17%, and in inflorescences - 0.23% of essential oil.
Keywords: Asian mint, Mentha asiatica Boriss., plants with essential oil, Ginzberg's apparatus, hydrodistillation method, medicinal plants.